Paul Gulden (1588-1658): royal servitor, creator of the first Polish-language professional dictionary, and promoter of the Torun theriac - Aleksander Karol Smakosz; Mateusz Dąsal (Polish Pharmaceutical Society, 2023)
In 1633, Władysław IV signed an important resolution of the Coronation Sejm. It updated the Titulo Aromata law of 1523. It established that pharmacists should be examined annually at the Akademia Krakowska (Cracow Academy). From now on, the pharmacy receives state regulation. Paweł Guldeniusz, the city, and royal apothecary was a witness to these developments. Because of the new challenges, he decided to compile a pharmaceutical dictionary, which he published in 1640. This work is the first Polish-language professional dictionary. Its publication made it possible to professionalize the profession and codify Polish-language terminology. The idea to write this dictionary likely originated when he was preparing his son for his pharmacy examinations. Today, we could call this work a didactic textbook or a script for young people wishing to acquire the profession of pharmacist. He included twenty-four questions and the answers to them to make it easier for pharmacist students to learn. In his life, he worked as both an ordinary apothecary and a royal apothecary. As such, he was directly accountable to the king and the court marshal. His tasks included supplying medicines and overseas foodstuffs to the court and attending to the king on his travels. In 1623. Guldenius arrived in Toruń, where, during the following two years, a plague epidemic claimed some five thousand citizens, including the then mayor Mark Mochinger, also a pharmacist. A few years before the Swedish Deluge and the siege of Toruń (1658), this city was attacked by the Swedes, resulting in another epidemic (1629). Consequently, Guldenius decided to develop a recipe for theriac (a universal remedy) to be administered to the inhabitants of the republic of Toruń. This recipe was printed in pamphlet form by Franz Schnellboltz. Teriak consisted of 65 ingredients, divided into seven classes of ingredients. These can be divided into the following categories: finished medicines and plant preparations, zoonotic raw materials, resins, spices, mushrooms, mineral substances, and other plant raw materials. The purpose of this article is to introduce the figure of Pavel Guldenius - pharmacist, creator of a professional dictionary, and promoter of the Torun theriac.